Ionic conduction and dielectric properties of yttrium doped LiZr2(PO4)3 obtained by a Pechini-type polymerizable complex route - Mariappan, Chinnasamy Ramaraj; Kumar, Parmod; Kumar, Ashok; Indris, Sylvio; Ehrenberg, Helmut; Vijaya Prakash, Gaddam; Rajan, Jose (Elsevier, 2018)
We report on the ion transport properties of Li1+xZr2-xYx(PO4)3 (0.05 ≤ x ≤ 0.2) NASICON type nanocrystalline compounds prepared through a Pechini-type polymerizable complex method. Structural properties were characterized by means of powder X-ray diffraction, Raman spectroscopy and electron microscopy with selected area electron diffraction. Impedance spectroscopy was utilised to investigate the lithium ion transport properties. Y3+doped LiZr2(PO4)3 compounds showed stabilized rhombohedral structure with enhanced total ionic conductivity at 30 °C from 2.87 × 10−7 S cm−1 to 0.65 × 10−5 S cm−1 for x=0.05 to 0.20 respectively. The activation energies of Li1+xZr2-xYx(PO4)3 show a decreasing trend from 0.45 eV to 0.35 eV with increasing x from 0.05 to 0.20. The total conductivity of these compounds is thermally activated, with activation energies and pre-exponential factors following the Meyer-Neldel rule. The tanδ peak position shifts to the high-frequency side with increasing yttrium content. Scaling in AC conductivity spectra shows that the electrical relaxation mechanisms are independent of temperature.